The Protective Effect of Xanthone via Malondialdehyde and Superoxide DismutaseExpression on Mice Sertoli cell Induced by 2-Methoxyethanol - Ernawati; Zufra Inayah; Sri Agus Sudjarwo (Indian Journal of Forensic Medicine & Toxicology, 2021)
The antioxidants can be used for protective in oxidative stress that is one of the important mechanisms of 2-methoxyethanol (2-ME)-induced testis toxicity. The current study was carried out to evaluate The protective effect of xanthone via Malondialdehyde (MDA) and Superoxide Dismutase (SOD) expression on mice Sertoli cell induced by 2-Methoxyethanolon the Sertoli cell number induced by 2-ME in mice. The study used 35 male mice divided into 5 groups: control group (mice were given daily with water purified by distillation); 2-ME group (mice were given daily with 2-ME 200 mg/kg BW orally once in a day for 35 days); and the treatment group ( mice were given the xanthone 60 mg, 120 mg, and 240 mg/kg BW orally once in a day for 38 days, and on the 3th day, were given 2-ME 200 mg/kg BW one hour after the xanthone administration). After 38 days, the testis tissues were collected to evaluate the histological of Sertoli cell number, and also evaluated the immunohistochemical of MDA and SOD expression on Sertoli cell. The result showed that 2-ME administration significantly increased MDA expression, and decreased both SOD expression and the number of Sertoli cells. However, the treatment of xanthone significantly decreased MDA expression, and increased the expression of SOD of the Sertoli cell in the immunohistochemical. Xanthone also significantly increased the Sertoli cell number in histopathological evaluation. In conclusion, From the results of this study demonstrated that xanthone is able to protect Sertoli cell number in mice treated with 2-ME through decreasing MDA and increasing SOD.